2021
DOI: 10.1186/s13018-021-02219-6
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral percutaneous vertebroplasty for osteoporotic lumbar compression fractures: a comparative study between transverse process root-pedicle approach and conventional transpedicular approach

Abstract: Purpose Percutaneous vertebroplasty (PVP) is a routine operation for the treatment of osteoporotic lumbar compression fractures (OLCFs). As is well known, unilateral puncture is a common method. However, with the conventional transpedicular approach (CTPA), the cement may be asymmetrically dispersed, so some surgeons use the transverse process root-pedicle approach (TPRPA). The objective of this study was to compare the clinical results and bone cement distribution of PVP for OLCF with unilater… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Unilateral PVP was associated with shorter operation time, and the height of anterior edge of vertebral body one week after operation was higher than that of Bilateral-group patients. Our results are in agreement with the study of Zhang et al 12 that indicated that the operation risk of unilateral PVP approach is smaller than that of bilateral PVP, and speculated that the operation time and X-ray irradiation time of bilateral approach are longer. As cement leakage is one of the most frequent complications of PVP, the intraoperative injection of bone cement on one side may increase the possibility of leakage on the other side, thus potentially increasing the risk, associated with the bilateral approach.…”
Section: Discussionsupporting
confidence: 93%
“…Unilateral PVP was associated with shorter operation time, and the height of anterior edge of vertebral body one week after operation was higher than that of Bilateral-group patients. Our results are in agreement with the study of Zhang et al 12 that indicated that the operation risk of unilateral PVP approach is smaller than that of bilateral PVP, and speculated that the operation time and X-ray irradiation time of bilateral approach are longer. As cement leakage is one of the most frequent complications of PVP, the intraoperative injection of bone cement on one side may increase the possibility of leakage on the other side, thus potentially increasing the risk, associated with the bilateral approach.…”
Section: Discussionsupporting
confidence: 93%
“…Finite element analysis is an emerging biomechanical research method, which divides the target structure that is difficult to analyze into a finite number of unit aggregates, and it is used to accurately simulate the structure of the spine and internal fixation. By applying different loads, the biomechanical responses of the spine and internal fixation were obtained qualitatively and quantitatively, and targeted prevention methods were proposed to guide the surgical design [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cement leakage could be a serious complication, 20 correlated with the amount of bone cement injection, the pressure of bone cement perfusion, and rupture of perivertebral cortex 51–53 . In the conventional unilateral approach, the needle needs to be excessively introverted to inject cement into the contralateral side of the vertebral body, which may lead to impairment of the pedicle inner cortical bone and paravertebral nerve injury 54 . Additionally, unilateral puncture is demanding at the thoracic level, while bilateral approaches may contribute to cement distribution and reduce the rate of epidural cement leakage 55 .…”
Section: Discussionmentioning
confidence: 99%